Generation of a heterozygous p53 R249S mutant human embryonic stem cell line by TALEN-mediated genome editing - Huo, Zijun; Tu, Jian; Xu, An; Li, Yan; Wang, Donghui; Liu, Mo; Zhou, Ruoji; Zhu, Dandan; Lin, Yu; Gingold, Julian A.; Yen, Chia-Jui; Xiao, Haipeng; et al. (Stem cell research, 2019)
As one of the most essential genome guardians, p53 and its mutants have been suggested associated with many types of cancers. Many p53 mutants function induce unique phenotypes, including carcinogenesis, metastasis, and drug resistance. The p53(R249S) mutation is the most prevalent and specific mutation associated with liver cancer development. Here, we demonstrate the generation of a heterozygous p53(R249S) mutation in the H9 human embryonic stem cell line using TALEN-mediated genome editing. The generated cell line maintains a normal karyotype, a pluripotent state and the in vivo capacity to develop a teratoma containing all three germ layer tissues.